Anti-reflection coating effects on beam performance of spiral-fed silicon lens antennas for THz communication - Hossain, A. K. M. Zakir; Azam, S. M. Kayser; Ibrahimy, Muhammad Ibn; Abd. Aziz, Mohamad Zoinol Abidin; Nor, Mohd. Khanapiah; Uddin, Jasim (IEEE, 2025)
This paper presents a numerical investigation of anti-reflection coating (ARC) effects on the beam performance of a spiral-fed half-hemispherical silicon lens antenna for terahertz (THz) communication up to 3.5 THz. Four single-layer ARC materials - SU-8, PTFE, HDPE, and polystyrene - are compared against the non-coated (NC) case. Key metrics including directivity, sidelobe level (SLL), back lobe level (BLL), and front-to-back ratio (FBR) are investigated. Results show SU-8 achieving the highest performance, with directivity of 26.6 dBi, SLL of –17.8 dB, and FBR of 25.32 dB at 3.5 THz. These findings provide valuable design guidelines for optimizing ARC selection in high-performance THz lens antennas for communication and sensing applications.